2004
DOI: 10.1007/s00122-004-1611-2
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of resistance against the beet cyst nematode from radish (Raphanus sativus) to rape (Brassica napus) by monosomic chromosome addition

Abstract: In rape ( Brassica napus), no resistance to the beet cyst nematode (BCN) Heterodera schachtii is available. This study was carried out to determine the specific chromosome(s) of resistant radish ( Raphanus sativus) carrying the gene(s) for nematode resistance as a prequisite to convert rape from a host into a trap crop for this pest. A Raphanobrassica progeny of 25 plants was analyzed which segregated for all nine chromosomes of the Raphanus genome in a genetic background of synthetic rape. The number of radis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
55
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 27 publications
(27 reference statements)
2
55
1
Order By: Relevance
“…Radish (Raphanus sativus L.) is cultivated worldwide. It possesses desirable agronomic characters, such as resistance to white rust (Albugo candida) [12], BCN (Heterodera schachtii) [13,14] and culbroot (Plasmodiophora brassicae) [15], as well as resistance to pod shattering [16]. Besides, various related wild species have attracted research attention as potential germplasms for improvement of Brassica crops [17].…”
Section: Introductionmentioning
confidence: 99%
“…Radish (Raphanus sativus L.) is cultivated worldwide. It possesses desirable agronomic characters, such as resistance to white rust (Albugo candida) [12], BCN (Heterodera schachtii) [13,14] and culbroot (Plasmodiophora brassicae) [15], as well as resistance to pod shattering [16]. Besides, various related wild species have attracted research attention as potential germplasms for improvement of Brassica crops [17].…”
Section: Introductionmentioning
confidence: 99%
“…Radish possesses agronomically useful traits such as resistances to beet cyst nematode (Heterodera schachtii) Krens 1992, Peterka et al 2004), clubroot (Plasmodiophora brassicae) (Ashizawa et al 1980) and white rust (Albugo candida) (Kolte et al 1991) and cytoplasmic male sterility (CMS) (Ogura 1968, Ikegaya 1986a, 1986b. Other Brassicaceae crops often lack these traits, and a large number of rape cultivars are susceptible to beet cyst nematode (Peterka et al 2004) and clubroot (Ashizawa et al 1980). Therefore, radish can be used as a nuclear and/or cytoplasm donor plant for the modification of rape.…”
Section: Introductionmentioning
confidence: 99%
“…In Brassicaceae with a number of important agricultural crops, several MAL series have been successfully bred through interspecific and intergeneric hybridizations to Communicated by T. Terachi Received August 25, 2008. Accepted February 19, 2009 express their phenotypic characteristics (Kaneko et al 1987, 2001, Quiros et al 1987, Jahier et al 1989, Struss et al 1991, Chen et al 1992, Srinivasan et al 1998, Bang et al 2002, Peterka et al 2004. These MALs have been also analyzed to locate the agronomic traits and gene(s) on the added chromosome (Zhu et al 1993, Chévre et al 1996, Kaneko et al 1996, Chen et al 1997, Peterka et al 2004, Bang et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, rape (Brassica napus L. 2n = 38, AACC), which includes winter and spring oilseed, fodder and vegetables rape forms, is today the most-widely cultivated crop species in the crucifer family (Brassicaceae), and a large number of rape cultivars are susceptible to beet cyst nematode (Peterka et al 2004) and clubroot (Ashizawa et al 1980). Therefore, radish is an important genetic resource for the breeding of rape.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kaneko et al (1996) found that the turnip mosaic virus (TuMV) resistance gene(s) was located on the f-chromosome of kale using a R. sativus-B. oleracea MAL series, and Peterka et al (2004) found that the beet cyst nematode (BCN) resistance gene(s) was located on the d-chromosome of radish using a B. napus-R. sativus MAL series.…”
Section: Introductionmentioning
confidence: 99%